Clinicopathological Evaluation of Seronegative Arthritis in a Tertiary Care Hospital of Bangladesh (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: The seronegative arthritis is a heterogeneous group of inflammatory rheumatic diseases with predominant involvement of axial, peripheral joints and enthesitis. All of these have some distinct as well as some overlapping features, characteristic peripheral asymmetrical lower limb involvement and a negative rheumatoid factor. Involvement of joints is usually oligoarticular but rarely polyarthritis may be present. Diagnosis is usually made from clinical features rather than investigations.Objective: To evaluate the seronegative arthritis clinicopathologically by collecting and analyzing the relevant informations.Materials and Methods: A descriptive cross-sectional prospective study was conducted at Combined Military Hospital, Chittagong from November 2015 to October 2016. A total 74 patients of suspected seronegative arthritis were included. Detail socio-demographic data were collected from the informant and recorded in structured case report form. Clinical examination and relevant investigations were done meticulously to confirm the aetiology of seronegative arthritis.Results: Maximum number of patients was in the 3rd to 4th decade (62.1%), mean age of the patient was 37.4±8.7 and 38.7±8.1 years in male and female respectively. Malefemale ratio was 2.65:1. Symmetrical sacroiliitis was found in 15(20.2%) patients, asymmetrical sacroiliitis in 36(48.6%) and in 23(31.2%) cases sacroiliac joint was not involved. Common aetiology for seronegative arthritis showed that, reactive arthritis recognized in majority of patients 29 (39.1%) and second most common cause was seronegative rheumatoid arthritis in 23(31%) patients.Conclusion: The Seronegative arthritis is a social, economical and health-care burden. Patients who develop 66 JAFMC Bangladesh. Vol 12, No 2 (December) 2016 arthritis have high disability, discomfort and loss of quality of life. Seronegative arthritis is an interesting group of related conditions with overlapping features and genetic and familial association. That may alert the primary care physician to attain possible diagnosis of spondyloarthritis and to consider a rheumatological opinion.Journal of Armed Forces Medical College Bangladesh Vol.12(2) 2016: 66-70